Word forms - how do we acquire them? - Jelaska, Zrinka (2000)
Word formation is an interesting linguistic topic, however, there is much more elaborated approach in the theoretical linguistics than in the linguistics of child language. Cognitive theory of prototypes could serve us as an adequate tool in analysing the process of word formation in children. One should be very careful in doing any type of both qualitative and quantitative analysis, due to the fact that the application of adult word formation patterns can often be misleading when interpreting child language data.